A farming system analysis of improved cassava technology - Lynam, JL (International Center for Tropical Agriculture, 1979)
The role of on-farm testing in the development of new cassava technology at the Centro Internacional de Agricultura Tropical (CIAT) is described in detail. On farm cassava trials have established a link between the research program and farms in the 1st stages of technology development. These trials become an integral part of research testings and evaluation; a systems approach is utilized. For crop programs a systems component at the final stage of the evaluation process is considered most effective. Farm trials fulfill the multiple objectives of problem identification, technology validation, and assessment of adoption constraints. The analytical power increases with the no. and diversity of the target area. The role of international cooperation in the modification of technology and the complexity of a farming system are highlighted. (CIAT)